Wheat Germ Agglutinin physisorption on Love Surface Acoustic Wave sensor for biofluid analysis - Martin Millicovsky; Luis Schierloh; Pablo Kler; Gabriel Muñoz; Matias Machtey; Martin Zalazar (Sensing and Bio-Sensing Research, 2025)
Biosensors play an essential role in the detection of biomarkers, enabling precise and early diagnosis as well as effective monitoring of diseases. However, conventional immobilization techniques for biosensors, such as covalent attachment and silanization, often require harsh chemical treatments that can alter the structure and activity of bioreceptors, limiting their effectiveness. As an alternative, physisorption offers a milder approach, preserving biomolecular activity by relying on non-covalent interactions. When combined with the Love Surface Acoustic Wave (LSAW) transducer—a highly sensitive technology for biosensing applications—physisorption presents a promising strategy for developing efficient biosensors. In this study, a gold-coated LSAW sensor was used to investigate the physisorption of Wheat Germ Agglutinin (WGA) lectin. A sensing system prototype was developed and characterized to assess sensor response across different WGA concentrations in a pH9 buffer aligned with WGA isoelectric point. The obtained biosensor was tested with human reflex tears at different dilution levels to evaluate the signal response of putative WGA-binding molecules. Results confirmed that physisorption is a robust and reliable immobilization technique. Moreover, integrating LSAW sensors with physisorption creates an innovative biosensing strategy, enabling high-sensitivity detection in complex biological fluids. This advancement underscores its significant potential for supporting tear-based diagnostics and expanding its applications in biomedical analysis.